Increased concentrations of nitrite in synovial fluid and serum samples suggest increased nitric oxide synthesis in rheumatic diseases. - Farrell, A J (1992)
Cytokines induce nitric oxide synthesis by endothelial cells, macrophages and polymorphonuclear leucocytes, indicating a role for nitric oxide in inflammatory processes. Nitric oxide production was therefore measured indirectly as nitrite in serum and synovial fluid samples from patients with rheumatoid arthritis (RA) and osteoarthritis (OA) together with serum samples from healthy volunteers matched for age and sex. Serum nitrite concentrations in patients with RA and OA were significantly higher than in controls. In both disease groups synovial fluid nitrite was significantly higher than serum nitrite, implying nitric oxide synthesis by the synovium. Serum and synovial fluid nitrite concentrations in RA were also significantly higher than those in OA. These data show increased nitric oxide production in RA and OA and suggest a role for nitric oxide as an inflammatory mediator in rheumatic diseases.